JAK2 Rearrangements Are a Recurrent Alteration in CD30+ Systemic T-Cell Lymphomas With Anaplastic Morphology. (July 2021) - Fitzpatrick, Megan J.; Massoth, Lucas R.; Marcus, Chelsea; Vergilio, Jo-Anne; Severson, Eric; Duncan, Daniel; Ramkissoon, Shakti H.; Hasserjian, Robert P.; Kim, Annette S.; Sohani, Aliyah R.; Williams, Erik A.; Nardi, Valentina
Abstract : Peripheral T-cell lymphoma (PTCL) comprises a heterogenous group of rare mature T-cell neoplasms. While some PTCL subtypes are well-characterized by histology, immunophenotype, and recurrent molecular alterations, others remain incompletely defined. In particular, the distinction between CD30 + PTCL, not otherwise specified and anaplastic lymphoma kinase (ALK)-negative anaplastic large cell lymphoma can be subject to disagreement. We describe a series of 6 JAK2 rearrangements occurring in a cohort of 97 CD30 + ALK − PTCL (6%), assembled after identifying an index case of a novel PABPC1-JAK2 fusion in a case of ALK − anaplastic large cell lymphoma with unusual classic Hodgkin lymphoma (CHL)-like features. Fusions were identified using a comprehensive next-generation sequencing based assay performed between 2013 and 2020. Five of 6 cases (83%) showed JAK2 rearrangements with 4 novel partners: TFG, PABPC1, ILF3, and MAP7, and 1 case demonstrated a previously described PCM1-JAK2 fusion. By morphology, all cases showed anaplastic large cells and multinucleated Reed-Sternberg–like cells within a polymorphous inflammatory background with frequent eosinophilia reminiscent of CHL. By immunohistochemistry, atypical large cells expressed CD30 with coexpression of at least 1 T-cell marker, aberrant loss of at least 1 T-cell marker and, in 4 of 5 cases stained (80%), unusual CD15 coexpression. These findings suggest that a subset of CD30 + ALK − systemic PTCL with anaplastic morphology carry JAK2 rearrangements, some of which appear to show CHL-like morphologic features. The presence of JAK2 rearrangements in cases of CD30 + PTCL augments current classification and may provide a therapeutic target via JAK2 inhibition.